História de alfabetizadoras Uberlandenses: modos de fazer no Grupo Escolar Bom Jesus 1955 a 1971 - Lima, Michelle Castro (2011)
The aim of this study was to construct, from the practices experienced by some literacy teachers, the History of Literacy in the primary school Bom Jesus, in the period 1955 to 1971. In this study, we could identify some relevant issues of the practices of these literacy teachers. The process of child literacy followed the patterns dictated by the Teaching Program for Primary Elementary of Minas Gerais. We analyzed the booklets: O Livro de Lili, As Mais Belas Histórias (Os Três Porquinhos) and Caminho Suave, that were always mentioned by literacy teachers during the entire study period. However, in analyzing the practices of literacy teachers, from the interviews, we identified what was preached, the use of the Global method, but few could really alphabetize with this method. The booklet Smooth Path (Caminho Suave) was present throughout the study period, being used to educate those students who could not keep up with the Global method. According to the literacy teachers interviewed, to work with the Global method, students had to be dedicated, otherwise they could not learn. We used the New Cultural History as the theoretical support, which brings new research possibilities and sources. Thus, oral history is crucial to the achievement of this study because it is from the voices of the own literacy teachers that build the history of literacy in the primary school Bom Jesus. We sought to identify those who have been the literacy teachers to understand which representations and appropriations made by them during that period and we tried to build a part of the history of literacy in Uberlandia. After the research we understood that the teachers, throughout their lives, were formed as literacy teachers. The results show that the practices are laden with value and representations that these professionals have built and build throughout the practice of primary teaching. Thus, their practices go beyond the rules laid down by school and bodies responsible for education in Minas Gerais.